Implementasi Nilai Pancasila dalam Etika Komunikasi pada Calon Guru Profesional sebagai Fasilitator - Natalia Syafitri Br Marpaung; Syafruddin Pohan; Adelina Br Marpaung; Anna Safitri (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2023)
Discussion related to communication ethichs is very urgent in determining the wight and quality of a communication or interaction process carried out both individually and by the people of a nation. This paper examines the related procedural dan substantial values that underlie the ethics of Indonesian communication based on Pancasila. This paper is purely a literature study with qualitative methods where the main data source is obtained from books or literature that discussed the value of Pancasila. therefore, this study is expected can inspire Indonesian peple to build a civilized communication style in the face of changing times which is effected by the communication media industry revolution.